2016
DOI: 10.1186/s12302-016-0097-2
|View full text |Cite
|
Sign up to set email alerts
|

Levels of DNA methylation and transcript accumulation in leaves of transgenic maize varieties

Abstract: BackgroundPrior to their release in the environment, transgenic crops are examined for their health and environmental safety. In addition, transgene expression needs to be consistent in order to express the introduced trait (e.g. insecticidal and/or herbicide tolerance). Moreover, data on expression levels for GM events are usually required for approval, but these are rarely disclosed or they are considered insufficient. On the other hand, biosafety regulators do not consider epigenetic regulation (e.g. DNA me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 87 publications
1
7
0
Order By: Relevance
“…However, the insertion of the transgene stabilized the massive loss of mC in pOsNAR2.1-OsNAR2.1. The tissue culture process can cause the loss of methylation in both WYJ7 and NP ( Figure 1a) according to both our results and those of Stroud, et al [20], but pOsNAR2.1-OsNAR2.1 in WYJ7 showed stabilization of the loss rather than pUbi-OsNAR2.1 in NP. Therefore, we consider that overexpression of OsNAR2.1 is not the reason behind the stabilization.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, the insertion of the transgene stabilized the massive loss of mC in pOsNAR2.1-OsNAR2.1. The tissue culture process can cause the loss of methylation in both WYJ7 and NP ( Figure 1a) according to both our results and those of Stroud, et al [20], but pOsNAR2.1-OsNAR2.1 in WYJ7 showed stabilization of the loss rather than pUbi-OsNAR2.1 in NP. Therefore, we consider that overexpression of OsNAR2.1 is not the reason behind the stabilization.…”
Section: Discussionsupporting
confidence: 89%
“…Previous research has reported that phenotypes are influenced by both genetic and epigenetic mechanisms [20,55,56]. Epigenetic modifications caused by the tissue culture process occur in an apparently random manner and it is thus difficult to predict phenotypic changes resulting from these modifications [4,5,7,57,58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stable transgene expression and heritability are key factors for the development and application of transgenic crops. Environmental factors, such as soil salinity, water accessibility and temperature all play crucial roles in Bt transgene expression 50 , 51 . Trtikova et al found that the Cry1Ab expression in MON 810 maize under hot/dry stress was significantly lower than that under optimal conditions 52 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to molecular characterization, NGS facilitates transcriptome pro ling [7] and can elucidate the potentially altered expression pro les of genes anking the transgene insert. Recently, highthroughput sequencing combined with "-omics" pro ling technologies, including transcriptomics, proteomics and metabolomics, has been widely used to analyze both target and unexpected effects [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%